(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Aim: to compare the effectiveness of complex drug treatment of patients with toxoplasma retinochoroiditis. Methods: A total of 33 patients (45 eyes) diagnosed with toxoplasma retinochoroiditis were examined at the Republican Specialized Scientific and Practical Medical Center of Eye Microsurgery (RSSPMCEM). Among them were 13 men (39.3%) and 20 women (60.7%). The patients’ age ranged from 19 to 56 years. Depending on the proposed treatment, the patients were divided into 2 groups. I. the main group. All patients in the main group were recommended to use Spiramycin 3,000,000 IU orally, 1 tablet once a day for 14 days, intramuscular injections of Immunomodulin 0.01% - 1 ml - 1 time per day - 10 days, parabulbar injections of Dexamethasone 0.5 ml 1 time per day for 5 days in the affected eye, as well as instillation of drops of Bromfenac 0.09% 1 drop 2 times a day - a month. II. Control group. All patients in the control group were recommended to use Spiramycin 3,000,000 IU orally, 1 tablet once a day for 14 days, parabulbar injections of Dexamethasone 0.5 ml once a day for 5 days in the affected eye, as well as instillation of Bromfenac 0.09% drops, 1 drop 2 times a day - a month. Results: Our study revealed that a pronounced functional result was achieved after 3 months of treatment, and positive dynamics were observed throughout the entire observation period. Conclusion: The additional use of immunomodulatory therapy demonstrated greater efficacy in the treatment of toxoplasma retinochoroiditis over six months. The main group showed greater statistically significant improvements in BCVA (0.41±0.05 to 0.68±0.05) compared to the control (0.43±0.05 to 0.58±0.05), RNFL thickness increased to 82 ±1.5 µm from 78±1.6 µm, and macular edema decreased to 278±3.8 µm from 312±4.2 µm. Despite structural disorganization persisting, immunomodulatory therapy demonstrated a significant advantage in improving functional and anatomical outcomes